Sustainable Homestay Tourism for Enhancing Rural Livelihood in the Uttarakhand Himalaya: A Study of the Tons River Basin - Prasad Sati Vishwambhar; Banergee Surajit (BIO Web of Conferences)
The Himalayan region provides a suitable basis for practicing various types of tourism due to its unique and spectacular landscape, varied climate, forest diversity, and rich cultural heritage. However, the people of the Himalayan region face poverty, and the area lacks adequate infrastructure, particularly in terms of accommodation and transportation. Sustainable homestay tourism can enhance rural livelihoods and promote various forms of tourism in the Himalaya. This study examines the role of sustainable homestay tourism in enhancing rural livelihood in the Uttarakhand Himalaya. Data were collected from the secondary sources and through case studies of five villages located along the Tons River valley. A report of homestay tourism of the State Government was considered for gathering data. For the case study, the heads of two households from each village were interviewed, totalling 10 interviewees. Each interviewee operates a homestay for tourists, with the number of available beds ranging from a minimum of four to a maximum of ten. However, the quality of the homestays is not optimal. This study suggests that more farmers should engage in homestay tourism, offering suitable accommodation, local food and beverages, and cultural performances that reflect the heritage of the region. Sustainable homestay tourism can enhance rural livelihoods while strengthening the region’s cultural identity.